On pressure disturbance waves - Moreira, R.M. (2015)
Pressure disturbance waves are computed via a fully nonlinear, unsteady, boundary integral formulation for various Froude numbers. Three moving pressure distributions are introduced in the numerical model to evaluate the produced wave patterns in a channel. For Froude numbers equal to one, classical runaway solitons are obtained on the fore of the moving pressure patch whereas "stern" waves are radiated away. "Step-like" pressure distributions give different responses to the free-surface flow, with upward breaker jets and steeper "stern" waves. For supercritical and subcritical flows, steady solitons and stationary trenches moving at the same speed of the pressure distribution are obtained, respectively. Nonlinear results show that the wave field is significantly affected by the chosen moving pressure distribution, with breaking "bow" waves and steeper "stern" waves when "step-like" pressure functions are used.